2017
DOI: 10.2196/jmir.6631
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Text Messaging to Improve Medication Adherence and Viral Load in a Vulnerable Canadian Population Living With Human Immunodeficiency Virus: A Repeated Measures Study

Abstract: BackgroundCombination antiretroviral therapy (cART) as treatment for human immunodeficiency virus (HIV) infection is effective and available, but poor medication adherence limits benefits, particularly in vulnerable populations. In a Kenyan randomized controlled trial, a weekly text-messaging intervention (WelTel) improved cART adherence and HIV viral load (VL). Despite growing evidence for short message service (SMS) text-message interventions in HIV care, there is a paucity of data utilizing these interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 54 publications
0
45
0
Order By: Relevance
“…There is a significant body of literature on text messaging as a means of, for instance, supporting people with chronic illness; [46][47][48] facilitating adherence and/or attendance; [49][50][51][52] conveying results of tests; 53 or sending health promotion messages. [54][55][56][57] Systematic reviews have indicated that text messaging can be effective in facilitating short-term behaviour and medication adherence in particular.…”
Section: Text Messaging and E-mailmentioning
confidence: 99%
“…There is a significant body of literature on text messaging as a means of, for instance, supporting people with chronic illness; [46][47][48] facilitating adherence and/or attendance; [49][50][51][52] conveying results of tests; 53 or sending health promotion messages. [54][55][56][57] Systematic reviews have indicated that text messaging can be effective in facilitating short-term behaviour and medication adherence in particular.…”
Section: Text Messaging and E-mailmentioning
confidence: 99%
“…8, Of these 26 studies, 23 studies used SMS alone for reminders, and 3 used SMS plus counseling as noted in ►Table 1. Six reports were from the United States; [35][36][37][42][43][44] three each from Kenya 8,31,40 and South Africa; 28,39,48 two each from Uganda, 38,45 China, 34,47 and Cameroon; 30,41 and one each from Italy, 26 Brazil, 29 Nigeria, 32 New Zealand, 27 India, 33 Argentina, 46 Canada, 49 and Malaysia. 50 The types of studies included 19 RCTs, 8,27,[29][30][31][32][34][35][36]38,39,[41][42][43][44][45]47,50 three prospective cohort studies, 26,37,46 two ambidirectional studies (retrospective/prospective cohort study...…”
Section: Resultsmentioning
confidence: 99%
“…The primary outcomes addressed in the studies included one ART usage among study participants, 40 one adherence measured through prescription refills, 48 two viral load adherences, 37,46 six adherences over time, 31,33,34,38,39,43 and 16 self-reported adherences (►Table 2). 8,[26][27][28][29][30]32,35,36,41,42,44,45,47,49,50 Adherence interventions were measured as self-report, ART usage, adherence over time using a medication event monitoring system (MEMS) or an electronic adherence monitoring device, such as Wisepill, pharmacy refills, pill count, and clinical outcomes (viral load, HIV-ribonucleic acid [RNA] suppression, and cluster of differentiation 4 [CD4] count). Additionally, a summary of the outcome data, adherence assessment, metrics, relative effect (risk and odds ratios [OR]), and a measure of precision (95% confidence interval [CI]) for each study are shown in ►Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Despite advances in the development of text messaging approaches to promoting adherence to various aspect of HIV care, there is a paucity of behavioral mHealth interventions research on people living with HIV and comorbid alcohol and other substance use disorders [52][53][54]. While at least one recent study addressed this gap by recruiting vulnerable populations with one or more risk factors for disengagement from HIV care (e.g., mental illness, active substance use, poor baseline ART adherence) to receive a text messaging intervention [55], the intervention content addressed ART adherence, but not alcohol or drug use. Correspondingly, improvements were observed in ART adherence, but not substance use.…”
Section: Discussionmentioning
confidence: 99%